The Global Waste Trafficking and Its Correlates. (August 2020) - Favarin, Serena; Aziani, Alberto
Our understanding of illicit waste trafficking (IWT) is in its embryonic stages; most notably, the transnational nature of this phenomenon has hitherto been neglected in extant empirical research. This study provides the first analysis of the possible coorrelates of transnational IWT at a global level. Through recourse to information extracted from the official Basel Convention National Reports, we constructed a network of the most relevant IWT connections between 148 countries. Next, we quantitatively investigated the role of specific potential factors that influence the structure of this transnational network. Our results indicate that illicit waste is trafficked toward poorer and more insecure countries, primarily via former colonial connections. As such, IWT poses a direct threat to the sustainable development of these countries. Mere adherence to international treaties and promulgation of environmental laws does not in and of themselves explain whether a country is part of the global IWT network, although the establishment of dedicated courts and tribunals does reduce the risk of being a recipient of trafficked waste. Solid anticorruption measures and a strong rule of law increased the likelihood of being a source country in the IWT network, which, in turn, calls for a more global approach to the management of environmental issues.